Development and Expert Validation of Augmented Reality-Integrated Innovative Learning Materials on Plant Cells and Tissues for Problem-Based Learning: An Approach Using Aiken’s V - A Bashri; R P Puspitawati; Wisanti Wisanti; S Indana; P Yakub; R Rukmana; J Shodiq (LP. Ma'arif Janggan Magetan, 2026)
Augmented Reality (AR) has the potential to improve Problem-Based Learning (PBL) in higher education by easing the visualisation of difficult biological ideas and encouraging active participation. The purpose of this study was to assess the viability and content validity of AR-integrated teaching resources created for PBL. The study concentrated on the validation stage using the ADDIE development paradigm and included three expert validators in instructional design, educational technology, and biology education. Aiken's V was used to evaluate content validity in terms of language appropriateness, presentation viability, and topic feasibility. To enhance the teaching materials, qualitative input from validators was also examined. The findings showed strong validity across all dimensions, with Aiken's V values more than 0.85. The display of AR elements, the clarity of instructions, and the alignment of learning exercises with problem-solving objectives were the main areas of expert recommendation. The quality and usability of the updated materials were improved by incorporating these suggestions. All things considered, the AR-integrated teaching resources showed excellent content validity and viability for postsecondary education. According to the results, the products are appropriate for use in classrooms and can help students grasp difficult biological ideas through interactive, technologically enhanced learning opportunities.